2014
DOI: 10.1158/0008-5472.can-14-0157
|View full text |Cite
|
Sign up to set email alerts
|

Complement C5a Receptor Facilitates Cancer Metastasis by Altering T-Cell Responses in the Metastatic Niche

Abstract: The impact of complement on cancer metastasis has not been well studied. In this report, we demonstrate in a preclinical mouse model of breast cancer that the complement anaphylatoxin C5a receptor (C5aR)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
198
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(210 citation statements)
references
References 46 publications
10
198
2
Order By: Relevance
“…To determine the time interval in which premetastatic changes occur, we tracked 4T1 cells that expressed GFP (4T1-GFP + ) and determined that tumor cells arrived to the lungs at day 20, at the earliest, as a result of spontaneous metastasis of the implanted breast tumors (12). Therefore, we concluded that the accumulation of AM and other immune cells observed in this model, using the same 4T1 clone ( Fig.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…To determine the time interval in which premetastatic changes occur, we tracked 4T1 cells that expressed GFP (4T1-GFP + ) and determined that tumor cells arrived to the lungs at day 20, at the earliest, as a result of spontaneous metastasis of the implanted breast tumors (12). Therefore, we concluded that the accumulation of AM and other immune cells observed in this model, using the same 4T1 clone ( Fig.…”
Section: Resultsmentioning
confidence: 86%
“…As negative controls, unstimulated cells were used. Cytokine production was assessed by standard intracellular cytokine staining procedure, as described in our earlier study (12). Staining for Ki-67 was performed after permeabilization with 70% chilled ethanol.…”
Section: Cell Isolation Stimulation and Facsmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of C5aR on MDSC modulation was also confirmed in the model Lewis lung carcinoma (3LL) (65). In addition, in a mouse model of breast cancer, C5aR was shown to promote metastasis by suppressing CD8 + T cell function and by enhancing Treg generation (66). In the same model, alveolar macrophages were shown to contribute to the metastatic potential in a C5aR dependent manner (67).…”
Section: Modulation Of Infiltration and Activation Of Immune Cells Bymentioning
confidence: 83%